Effect of air pressure on moisture transfer inside porous building materials. Issue 4 (22nd June 2018) - Fukui, Kazuma; Iba, Chiemi; Hokoi, Shuichi; Ogura, Daisuke
Abstract: The effect of air pressure on moisture transfer inside porous building materials cannot be omitted in cases where air cannot escape through the surface of the materials; in such cases, air is compressed by the movement of moisture. In this study, we conducted water‐absorption tests on a brick specimen. By comparing the result of the experiment on a specimen whose side surfaces were sealed with that of a specimen whose bottom surface was additionally sealed, it was demonstrated that the water‐absorption was evidently delayed in the latter case, wherein air could not escape from the specimen except for the top surface, through which water was absorbed. We also developed a numerical model based on the equations for simultaneous air and moisture transfer. The calculated result is reasonably consistent with the experimental result, which supports the validity of the model that includes the change in air pressure in the material and air loss through the top surface as air bubbles. By using this model, the behavior of the air and water inside the specimen was investigated in detail. Abstract : Water‐absorption tests were conducted on a brick specimen to confirm the effect of air pressure on moisture transfer inside porous building materials. The results of the experiments show that the moisture infiltration becomes significantly slow when air cannot escape from the specimen. Using simultaneous transfer model of air and moisture, the behavior of the air and moisture inside the specimen was investigated in detail.